2018
DOI: 10.3389/fimmu.2018.02965
|View full text |Cite
|
Sign up to set email alerts
|

Hidradenitis Suppurativa: A Systematic Review Integrating Inflammatory Pathways Into a Cohesive Pathogenic Model

Abstract: Background: The pathogenesis of hidradenitis suppurativa (HS) is not fully understood. This systematic review examined the latest evidence for molecular inflammatory pathways involved in HS as a chronic inflammatory skin disease.Methods: A systematic literature search was performed in PubMed/Medline and EMBASE from January 2013 through September 2017, according to the preferred reporting items for systematic reviews and meta-analyses (PRISMA). Findings on HS pathogenesis were also compared with those of other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
184
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(200 citation statements)
references
References 95 publications
7
184
0
Order By: Relevance
“…Inflammation plays an important role in the pathogenesis of HS. In LS, cytokines and chemokines, such as TNFα, IL1, IL6, IL10, IL12, IL17, IL23, interferon (IFN)γ, phosphodiesterase‐4, complement 5α, uteroglobulin, chemokine (C‐X‐C motif) ligand (CXCL)6, CXCL9, CXCL11, CX3CL1, CC‐chemokine ligand (CCL)2, CCL18, TLR2, soluble IL2 receptor are upregulated, as described in proteome studies . Especially IL23 has been shown to induce IL17‐producing T helper cells (Th17), which infiltrate the dermis in HS lesions .…”
Section: Discussionmentioning
confidence: 93%
“…Inflammation plays an important role in the pathogenesis of HS. In LS, cytokines and chemokines, such as TNFα, IL1, IL6, IL10, IL12, IL17, IL23, interferon (IFN)γ, phosphodiesterase‐4, complement 5α, uteroglobulin, chemokine (C‐X‐C motif) ligand (CXCL)6, CXCL9, CXCL11, CX3CL1, CC‐chemokine ligand (CCL)2, CCL18, TLR2, soluble IL2 receptor are upregulated, as described in proteome studies . Especially IL23 has been shown to induce IL17‐producing T helper cells (Th17), which infiltrate the dermis in HS lesions .…”
Section: Discussionmentioning
confidence: 93%
“…Other inflammatory mediators have been identified as compartmentalized between HS serum and lesional tissue by Kanni et al, [16] and it would be valuable to ascertain whether this also holds true for C5a. [17] This begs the question as to whether complement is a central component of the pathophysiology of HS alongside Th17 activation, or a secondary consequence (ie bystander) of inflammatory pathway activation and neutrophil activity. Based upon the serological results of Kanni et al, [15] complement inhibition has been identified as a potential therapeutic target in HS.…”
Section: Dys Reg Ul Ati On Of Complement Is a Sso Ciated With D Is mentioning
confidence: 99%
“…[17] Given the dual expression of C5aR1 and C5aR2 on dermal fibroblasts and mast cells, [29] complement dysregulation may also contribute to the activation of fibroblasts. Pruritus is also a common manifestation, which often goes under-reported.…”
Section: Ar1 and C 5ar 2 Are Pre S Ent On Fib Rob L A S Ts Ma mentioning
confidence: 99%
“…However, Notch dysregulation has also been identified in keratinocytes of other inflammatory dermatoses including psoriasis and atopic dermatitis . Animal knockout models of components of the GSC with resultant Notch dysregulation result in the development of dermal cysts and histological features of follicular occlusion, suggesting that aberrant Notch signalling is linked to the unique clinical and histological manifestations of HS . However, these models also rapidly develop multiple squamous cell carcinomas, which is not consistent with the typical progression of HS.…”
mentioning
confidence: 99%
“…Animal knockout models of components of the GSC with resultant Notch dysregulation result in the development of dermal cysts and histological features of follicular occlusion, suggesting that aberrant Notch signalling is linked to the unique clinical and histological manifestations of HS . However, these models also rapidly develop multiple squamous cell carcinomas, which is not consistent with the typical progression of HS. The precise role of Notch dysregulation as the primary driver in the molecular pathogenesis of HS is unclear.…”
mentioning
confidence: 99%